Semantic Anomalies in Uploads and Verbal Interactions on the TikTok Platform - Anisa Boangmanalu; Indri Serliana; Nurazizah; Nurul Hafni; Qonita Sholihat; Saiyidatu Syuhuri; Lina Sundana (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2026)
This study aims to identify errors in vocabulary usage in posts during verbal interactions on TikTok. Furthermore, it aims to correct and reduce the occurrence of incorrect word usage that does not correspond to the actual meaning among TikTok users. The object of study is analyzed from TikTok, starting with looking for forms of semantic errors such as Cosine Pair Errors (KPS), Inappropriate Word Choice Errors (KPTT), and Confused Pair Errors (KPT). This research method uses a qualitative descriptive method. Data sources are obtained from social media posts and verbal interactions on TikTok regarding videos, captions, and comments on TikTok. Furthermore, this researcher uses documentation techniques, namely by saving screenshots of videos or comments on TikTok. The results of the study include 12 words analyzed from TikTok posts, including bis, minta, ruku, mampu, recapitalisasi, usai, papak, kaka, preseden, lulus, and korban.